Binding of Molybdenum(VI) to Soyabean Protein by Physico-chemical Methods - SINGH, R.P.; SHARMA, A.; ARORA, S.K.; CHAUDHARY, R. (Asian Journal of Chemistry, 2010)
The interaction of molybdenum(VI) has been studied with soyabean protein using polarographic (at pH 5.57) and equilibrium dialysis (at pH 5.57, 7.50 and 9.30) methods. The intrinsic association constants and the number of binding sites have been calculated from Scatchard plots. The effect pH and temperatures on these constants were studied by equilibrium dialysis method. The number of sites available for binding with molybdate ions is much less than the actual number of cationic groups, which are 14, 11 and 10 at pH values 5.57, 7.50 and 9.30, respectively by equilibrium dialysis at 25 ºC. These nearly similar values were found at pH 5.57 by polarographic method at 25 ºC. The values of different thermodynamic parameters have been reported. The large positive entropy change of binding coupled with the small enthalpy change of binding have been interpreted to mean that the major contribution to the free energy of binding comes from the release of the solvent molecule from the molybdate-soyabean complex.